1D infinite helical water chain encapsulated in a supramolecular complex based on amino acid derivate. (22nd January 2016) - Yu, Fan; Li, Bao
ABSTRACT: An oligonuclear complex based on amino acid derivate had been synthesized and structurally characterized, which exhibits a three- dimensional (3D) supramolecular framework constructed from the mono-cobalt units and helical water chains stabilized in this complex. Additionally, the compound was characterized by thermogravimetric analysis (TGA), IR spectroscopy, and elemental analysis.